School Objects? When New Characters Enter the Scene - Gaspar da Silva, Vera Lucia; de Graca Cruz Dominues Amante, Lucia (Education Policy Analysis Archives, 2015)
In this article we reflect on the technologies challenges on teaching practice. Technologies are here understood as material components of pedagogical practice. Our purpose is to articulate a reflection that historically places the entrance of different objects into the educative scene, and resume some educational elements about their relations with different classical theoretical conceptions about the learning process, as well as their relationship with the current connectivist conceptions. It equates and discusses the difficult relationship between technological innovation and school, arguing for strengthening the teaching profession and highlighting the challenges faced by educators in the contemporary world in order to put the new technological objects in service of learning in schools in the digital age.